Correction: Introducing dip pen nanolithography as a tool for controlling stem cell behaviour: unlocking the potential of the next generation of smart materials in regenerative medicine. Issue 12 (1st June 2017) - Curran, Judith M.; Stokes, Robert; Irvine, Eleanore; Graham, Duncan; Amro, N. A.; Sanedrin, R. G.; Jamil, H.; Hunt, John A.
Abstract : Correction for 'Introducing dip pen nanolithography as a tool for controlling stem cell behaviour: unlocking the potential of the next generation of smart materials in regenerative medicine' by Judith M. Curran et al., Lab Chip, 2010, 10, 1662–1670.